2020
DOI: 10.25518/1780-4507.18464
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of promising high-yielding cashew (Anacardium occidentale L.) cultivars from Côte d'Ivoire

Abstract: Description of the subject. Cashew was introduced to Côte d'Ivoire in 1951 to control erosion and reforest cutover lands. From 1972 to 1980, natural forest plantations were converted to fruit orchards and were supplemented by the ‘Jumbo’ cashew variety imported from Brazil. Germplasm expeditions conducted in 2010 and 2014–2015 identified 209 high-yielding cultivars in the major cashew growing areas of Côte d’Ivoire. Although the morphological characteristics of these cultivars have been assessed, little is kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
1
6
2
Order By: Relevance
“…In Brazil, wild Brazilian populations of cashew were studied ( Dos Santos et al, 2019 ), and the genetic diversity in wild populations was higher than in domesticated ones, despite a weak distinction between wild and domesticated groups and with no correlation between genetic and geographical interpopulation distance. In Cô te d’Ivoire, cashew genetic diversity was studied using SSRs and the resultsnrevealed an overall heterozygosity deficit and a high intra-population genetic diversity among the screened cashew populations ( Kouakou et al, 2020 ), which is in accordance with the AMOVA results of this study where the most genetic diversity was depicted within populations. The results obtained from this study also agree with a recent study from Burkina Faso, where a substantial amount of genetic diversity was observed across the 18 cashew accessions screened with four SSRs ( Moumouni et al, 2022 ).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In Brazil, wild Brazilian populations of cashew were studied ( Dos Santos et al, 2019 ), and the genetic diversity in wild populations was higher than in domesticated ones, despite a weak distinction between wild and domesticated groups and with no correlation between genetic and geographical interpopulation distance. In Cô te d’Ivoire, cashew genetic diversity was studied using SSRs and the resultsnrevealed an overall heterozygosity deficit and a high intra-population genetic diversity among the screened cashew populations ( Kouakou et al, 2020 ), which is in accordance with the AMOVA results of this study where the most genetic diversity was depicted within populations. The results obtained from this study also agree with a recent study from Burkina Faso, where a substantial amount of genetic diversity was observed across the 18 cashew accessions screened with four SSRs ( Moumouni et al, 2022 ).…”
Section: Discussionsupporting
confidence: 87%
“…Considering the 11 populations studied from East Timor, population differentiation ( F ST = 0.129, Table 5 ) was relatively moderate in comparison to a previous study of cashew trees in Côte d’Ivoire ( Kouakou et al, 2020 ) where a low differentiation was indicative of a common origin. However, moderate differentiation could also be associated with the lower number of molecular markers used in this study (12 SSRs vs 18 SSRs in Kouakou et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations